Bangladesh : Can Conditional Cash Transfers Improve Nutrition? - World Bank (Washington, DC, 2015)
Policymakers and development groups are interested in innovative ways to deliver cash transfer programs and make an impact where it s needed most. In Bangladesh, World Bank researchers worked with the government to evaluate a pilot social protection program that conditioned transfers on primary school attendance, monthly growth monitoring for young children and monthly nutrition sessions for mothers. Payments were made to mothers via electronic cash cards. While the program had no effect on school attendance, it significantly boosted consumption of protein and other nutrition- rich foods, and reduced wasting. Based on the results, the nutrition-related part of the program is being scaled up with World Bank assistance to reach 600,000 of the poorest households across Bangladesh, potentially benefitting 2.7 million people. Bangladesh reduced the percentage of families living in poverty by almost a third over the past decade to 30 percent, but the country hasn t been as successful at cutting the rate of wasting and stunting among children. Bangladesh has one of the highest rates of malnutrition in the world and 41 percent of children below the age of 5 are stunted. About five million children are also out of school.